2007
DOI: 10.1016/j.toxlet.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics of endoplasmic reticulum stress inducer tunicamycin in the small intestine and liver of Nrf2 knockout and C57BL/6J mice

Abstract: This objective of this study was to investigate the toxicogenomics and the spatial regulation of global gene expression profiles elicited by Endoplasmic Reticulum (ER) stress inducer Tunicamycin (TM) in mouse small intestine and liver as well as to identify TM-modulated Nuclear Factor-E2-related factor 2 (Nrf2)-dependent genes. Gene expression profiles were analyzed using 45,000 Affymetrix mouse genome 430 2.0 array and GeneSpring 7.2 software. Microarray results were validated by quantitative real-time revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 40 publications
4
40
1
Order By: Relevance
“…Many phase II detoxifying genes, including glutathione S-transferase (GST) isoforms and GCLM, were found to be downregulated in an Nrf2-dependent manner (Nair et al 2007). Combined with the results from our study, it is likely that the observed down-regulation of the Nrf2-mediated response in the early study was due to the upregulation of Hrd1 by tunicamycin.…”
Section: Discussionsupporting
confidence: 65%
“…Many phase II detoxifying genes, including glutathione S-transferase (GST) isoforms and GCLM, were found to be downregulated in an Nrf2-dependent manner (Nair et al 2007). Combined with the results from our study, it is likely that the observed down-regulation of the Nrf2-mediated response in the early study was due to the upregulation of Hrd1 by tunicamycin.…”
Section: Discussionsupporting
confidence: 65%
“…The only change in gene expression that was similar to what is seen in the UPR was a 2.4-fold increase in HERPUD1 in the adult series. No other changes in expression of genes known to be altered during the UPR or that appear in previous high density oligonucleotide array analyses of the UPR (15)(16)(17)(18)(19)(20) reached significance in this study, including absence of the 2.5-3-fold increase in GRP78 and GRP94 and 3.1-3.9-fold increase in protein-disulfide isomerase and its related proteins.…”
Section: Gene Expression Profile In the Liver In Response To Accumulacontrasting
confidence: 60%
“…ER stress was induced using palmitate or tunicamycin as described previously (34). Palmitate induces ER stress through degradation of carboxypeptidase E (35), whereas tunicamycin, an inhibitor of N-linked glycosylation, inhibits dolichol pyrophosphate-mediated glycosylation of asparaginyl residues of glycoproteins (36). Because glucose concentration affects ER stress in ␤ cells (37), we performed these studies under low and high glucose conditions.…”
Section: Er Stressmentioning
confidence: 99%